2009
DOI: 10.1021/ol900502s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fused and Bridged Bicyclic Diazenium Salts by Intramolecular Cycloaddition

Abstract: Bicyclic diazenium salts were efficiently prepared by a Lewis acid mediated intramolecular cycloaddition. Terminal olefins provided mixtures of fused and bridged bicyclic diazenium salts. The alpha-chloroazo cycloaddition precursors were conveniently prepared from the corresponding phenyl hydrazones by treatment with chlorodimethylsulfonium chloride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Indeed, prior oxidation of the starting hydrazone to form an azoacetate, which can then cyclize under activation by a Lewis acid, may explain the formation of intermediate C . A similar type of cycloaddition with α‐chloroazo derivatives was recently reported by Brewer et al12 In the same study, they observed fast rearrangement of diazenium salts into hydrazonium salts, not unlike our proposition for the conversion of C into D (Scheme ).…”
Section: Resultssupporting
confidence: 87%
“…Indeed, prior oxidation of the starting hydrazone to form an azoacetate, which can then cyclize under activation by a Lewis acid, may explain the formation of intermediate C . A similar type of cycloaddition with α‐chloroazo derivatives was recently reported by Brewer et al12 In the same study, they observed fast rearrangement of diazenium salts into hydrazonium salts, not unlike our proposition for the conversion of C into D (Scheme ).…”
Section: Resultssupporting
confidence: 87%
“…With a convenient route to aryl-α-chloroazo alkenes in hand, we have begun to study the formation of bicyclic diazenium salts via intramolecular Lewis acid-mediated cycloaddition . For example, treating phenyl-α-chloroazo 12a with antimony pentachloride resulted in an intramolecular cycloaddition to provide fused bicyclic diazenium salt 13a as a single diastereomer in 88% isolated yield (entry 1, Table ).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Jochims and colleagues reported that α-chloroazo compounds (e.g., 3 , Scheme ) react with halophilic Lewis acids to provide 1-aza-2-azoniaallene cation intermediates (e.g., 4 ), which display reactivity reminiscent of Huisgen-type 1,3-dipolar compounds and undergo intermolecular [3 + 2] cycloaddition with alkenes to provide diazenium salt heterocycles (e.g., 5 ). We recently reported the preparation of more structurally complex bicyclic diazenium salts by rendering this Lewis acid-mediated process intramolecular . The success of this intramolecular cycloaddition in providing structurally complex heterocyclic products from simple starting materials encouraged us to explore the formation of bicyclic diazenium salts further and we present our results here.…”
Section: Introductionmentioning
confidence: 88%
“…4 Once formed, these cationic heteroallenes, which are 1,3-monopols, can react in concerted (3+2) cycloadditions with alkenes to give bicyclic diazenium salt products (Scheme 1, 1  3). [5][6][7] In addition, we have shown that these species, which can be thought of as imino-nitrenium cations, can react in C-H insertion reactions to give pyrazolines through a bonding stepwise but energy concerted amination process (Scheme 1, 4  6). 8,9 Scheme 1.…”
Section: Introductionmentioning
confidence: 99%